(untitled) (Scientific journal of the Fergana State University, 2023)
This article studies the composition of cosmetic creams. The negative impact of low-quality goods on human health and the country’s economy has been substantiated. Modern organoleptic and physicochemical methods for determining the quality of goods have been developed and introduced into the customs system.